Pengaruh Substitusi Tepung Ubi Jalar Kuning (Ipomoea batatas L.) dengan Tepung Kulit Ari Kedelai (Glycine max L.) Terhadap Karakteristik Snack Bar sebagai Alternatif Camilan Sehat - Uttami, Ni Kadek Dian Arya Rahayu; Nocianitri, Komang Ayu; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2025)
Snack bars are bar-shaped snacks that have nutrients such as protein, carbohydrates, fiber and vitamins. Most commercial snack bars use imported raw materials. The utilization of yellow sweet potato into snack bar raw materials was done to diversify local food. Yellow sweet potato had a lower glycemic index than wheat, is gluten-free, rich in vitamins, but low in protein and fiber. Therefore, soybean hull flour which had the potential as a source of fiber and protein is used as a substitute. The aim of this research was to assess the impact of substituting yellow sweet potato flour with soybean hull flour on snack bar characteristics and the appropriate substitution of yellow sweet potato flour with soybean hull flour to produce snack bars with the best characteristics. This research used a completely randomized design (CRD) with the treatment of substitution of yellow sweet potato flour with soybean hull flour such as 100:0, 90:10, 80:20, 70:30, 60:40, 50:50 each with three repetitions, so 18 experimental units were collected. The collected data were analyzed using variance analysis and followed by using DMRT's test. The finding indicated that the substitution of yellow sweet potato flour with soybean hull flour had an impacted on fat, ash, carbohydrate, protein, water, total calories, crude fiber content, hardness, taste, color, aroma score, overall acceptance, and texture of snack bars. Treatment 2 was chosen as the best treatment, including moisture content 16.67 percent, ash content 2.08 percent, protein 11.63 percent, fat 22.33 percent, carbohydrate 47.23 percent, crude fiber content 8.36 percent, total calories 436.51 kcal, hardness 16 N, texture and aroma are liked slightly with no beany flavor, the color, taste and overall acceptance are liked.